The Effect of Health Education on Early Detection of Diabetic Foot Wound Complications - Nourah Nazifa; Fahmi Ichwansysah; Nurjannah Nurjannah; Asnawi Abdullah; Basri Aramico (GLOBAL HEALTH SCIENCE GROUP, 2025)
The number of Diabetes Mellitus sufferers in Aceh is 2.4%. In 2023, the prevalence of Diabetes Mellitus sufferers in Southwest Aceh Regency is 4236 sufferers. One of the impacts of diabetes mellitus with diabetic foot ulcers is a 2.5 times higher risk of death compared to diabetes mellitus patients who do not experience diabetic foot ulcers. The purpose of this study was to analyze the effect of health education on increasing early detection of diabetic foot ulcer complications at Tengku Peukan Hospital. Quantitative research with a pre-experimental design approach. The population was 531 people and a sample of 228 people, selected through consecutive sampling. The instrument used SOP, PPT media education and a questionnaire to increase early detection of Diabetic Foot Ulcer complications. The statistical test used was the Wilcoxon Sign Rank test. The results of the analysis showed that there was a difference in early detection before and after education about diabetic foot ulcer complications with a p value = 0.000 (z = -13.091).